1969
DOI: 10.1103/physrevlett.23.677
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Structure in Measured TotalLi++ Li Charge Transfer and Comparison with Theory

Abstract: Measured Li + + Li total charge-transfer cross sections are reported and compared with the computed results of Peek, Green, Perel, and Michels based on an ab initio twostate calculation. Both experiment and theory show oscillatory structure in the cross sections with very good agreement in cross-section magnitude and oscillatory structure. There exist, however, small but important differences in the oscillation characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 7 publications
4
8
0
Order By: Relevance
“…Smith 4 has shown that such oscillations result from a two-state theory for resonant chargetransfer collision in which the difference between gerade and ungerade potentials passes through an extremum. Peek et al 5 have used the known potential difference curve of the Li 2 + molecule to calculate the oscillatory cross section for Li + -Li charge transfer, which is in good agreement with the experimental results of Perel et al 6 The term XI(R) defined by Eq. (4) is equal to one half the difference between the gerade and ungerade potential states of the Na 2 + molecule.…”
supporting
confidence: 66%
“…Smith 4 has shown that such oscillations result from a two-state theory for resonant chargetransfer collision in which the difference between gerade and ungerade potentials passes through an extremum. Peek et al 5 have used the known potential difference curve of the Li 2 + molecule to calculate the oscillatory cross section for Li + -Li charge transfer, which is in good agreement with the experimental results of Perel et al 6 The term XI(R) defined by Eq. (4) is equal to one half the difference between the gerade and ungerade potential states of the Na 2 + molecule.…”
supporting
confidence: 66%
“…These values for the states (1) 2 and (1) 2 (as illustration) are given in Table 4. The comparison of these values with other results is not possible, since they are given here for the first time.…”
Section: The Resultsmentioning
confidence: 98%
“…Collisions between alkali-metal ions have been studied since the early work of Perel et al [1,2], Daley and Perel [3],Aquilanti et al [4][5][6][7][8][9][10], Brunetti et al [11], Talk et al [12], Anderson et al [13], and Olsen et al [14]. These collisions play an important role in the different areas of the physics and chemistry of lowdensity plasma and ionized gases and provide detailed information about long-range interatomic potentials, scattering length [15], and excited-state radioactive life times.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali ion interactions with neutral atoms or molecules play an important role in different areas of physical and chemical systems in both gas and condensed matter, their behaviour being closely related with the ion kinetic energy. In the range of a few keV, the pioneering studies by Perel et al 1 and Aquilanti and Casavecchia 2 among others 3,4 showed that electron transfer leading to electronically excited states and neutral target excitation was the main non-adiabatic excitation process. More recently, and in the same energy range, systems involving heavier alkali ions and atoms have been studied by some of us 5 using also Mg atoms as targets, 6,7 complemented for (Rb-Mg) + with a multisurface dynamical study.…”
Section: Introductionmentioning
confidence: 99%